Exfoliation of Boron Nitride Platelets by Enhanced Interfacial Interaction with Polyethylene. Issue 3 (19th January 2016) - Tajaddod, Navid; Song, Kenan; Green, Emily C.; Zhang, Yiying; Minus, Marilyn L.
Abstract : Interfacial crystallization of ultrahigh molecular weight polyethylene on boron nitride (BN) platelets takes place under flow‐crystallization conditions. Experimental Raman and wide‐angle X‐ray diffraction analysis evidence suggests polymer drawing assists exfoliation of BN during drawing. Abstract : Hexagonal boron nitride (BN) platelets are used for fabrication of ultrahigh molecular weight polyethylene (UHMWPE)/BN composite fibers using a flow‐crystallization process. As‐spun fibers are subsequently drawn near the UHMWPE melting temperature. Interfacial crystallization of UHMWPE is observed on the surfaces of the BN platelets. Both X‐ray and Raman spectroscopy analysis of the drawn composite fibers show a significant decrease in the intensity of the signature BN peaks associated with the platelet interlayer spacing, as compared to undrawn samples. This suggests exfoliation of the BN platelets occurs during the fiber hot‐drawing process. Exfoliation of BN platelets is induced due to interfacial stress transfer between both components (i.e., UHMPWE and BN) within the composites. This stress transfer is facilitated by molecular rearrangement of polymer matrix during drawing (i.e., unfolding of the polymer chain). The changes in micro‐ and nanoscale morphologies due to unfolding of the polymer chains as well as simultaneous exfoliation of the BN platelets are fully characterized and show that these structural changes provide insight for understanding the property trends of the fibers.